Fabrication and properties of yttria, ceria doped zirconia-aluminia ceramic composites - Lyubushkin, R.A.; Ivanov, O.N.; Chuev, V.P.; Buzov, A.A. (Вопросы атомной науки и техники, 2011)
At present, zirconia-based ceramics are gaining popularity in dentistry, particularly in fixed prosthodontics. clinically, it is important that ceramic restorations reproduce the translucency and color of natural teeth. Zirconia based ceramics is a high performance material with excellent biocompatibility and mechanical properties, which suggest its suitability for posterior fixed partial dentures. Y₂O₃-stabilized tetragonal zirconia polycrystalline (YTZ/Al₂O₃) and CeO₂-stabilized tetragonal zirconia polycrystalline (CZA) ceramics with high-performance were prepared for dental application by use the wet chemical route, consolidated by cold isostatic pressing, and two-step sintering method. Physical and mechanical properties test results show that the bending strength, fracture toughness, and the density of full sintered ceramics suggest that the material is relatively suitable for dental restoration.